(untitled) (Global Journal of Medical Research, 2014)
Extraadrenal paraganglioma constitute only 10%. Among them paraganglioma outside usual distribution is less than 1%. Most of the cases are solitary and sporadic. Familial cases are also seen. They are associated with several syndromes. Extra-adrenal paragangliomas are rarely diagnosed preoperatively unless the lesion is functional. Paraganglioma of mesentery of small intestine are very rare. Till date 10 cases are reported and this is the eleventh case. This is the second case where the paraganglioma is in the anterior aspect of the mesentery of small intestine and 1st reported case involving the wall of jejunum. Our case is the youngest reported till date. We hereby report a case of 23 years male patient who presented to us with discomfort and mass per abdomen. Investigations revealed a mass in the mesentery of small bowel. Provisional diagnosis was GIST of jejunum. Laparotomy was performed mass was resected, histopathology and IHC revealed the diagnosis.